Growth and nutrients uptake of soybean (Glycine max L.) in response to cajeput waste compost and inorganic fertilizer. Issue 1 (June 2021) - Isnatin, U; Muhammad,; Rahayu,; Purnomo, D
Abstract: Productivity of Soybean in sandy soils is still low and cajeput waste is increasing in number. The purpose of this study was to determine the effect of the use of compost from cajeput waste and inorganic fertilizers to increase the growth and nutriens uptake of soybean. This research was conducted using a randomized block design, with treatment : control, NPK 150 kg/ha, compost 6 t/ha, compost 6 t/ha + NPK 50 kg/ha, compost 6 t/ha + NPK 100 kg/ha and compost 6 t/ha + NPK 150 kg/ha The results showed that soybeans fertilized by compost alone have dry weight of stem, N uptake and K uptake higher than without fertilizing at 26.19%, 23.21% and 36.11% respectively. Increasing the dose of NPK fertilizer combined with compost can increase N and K uptake, but reduce the number of root nodules. The highest dry weight of stem, N uptake and K uptake in compost fertilizer combined with NPK of 150 kg/ha were respectively 2.31 g / plant, 0.076 g / plant and 0.056 g / plant.